2010
DOI: 10.1024/0301-1526/a000053
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of carotid atherosclerosis in orthopantomograms and the risk for future cardiovascular events

Abstract: Evidence of carotid plaque revealed by OPGs in patients with previously known cardiovascular disease is no useful prognostic marker for MACE. Detection of carotid atherosclerosis by OPGs in these patients therefore has no clinical consequence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Atheromas often have been detected on the panoramic radiographs of neurologically asymptomatic male veterans; however, similar studies have not been conducted among female veterans ( 14 ). Hoke et al reported that there is no statistically significant association between the presence of CAC on panoramic radiographs and the presence of a significant carotid stenosis or the degree of carotid stenosis ( 4 ). In a study conducted by Masood et al, hypertension did not show a statistically significant association with CAC ( 6 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Atheromas often have been detected on the panoramic radiographs of neurologically asymptomatic male veterans; however, similar studies have not been conducted among female veterans ( 14 ). Hoke et al reported that there is no statistically significant association between the presence of CAC on panoramic radiographs and the presence of a significant carotid stenosis or the degree of carotid stenosis ( 4 ). In a study conducted by Masood et al, hypertension did not show a statistically significant association with CAC ( 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, finding symptoms and risk factors that predict CVA is important for prevention. Some of these risk factors include hypertension, myocardial infarction (MI), high cholesterol smoking and diabetes ( 3 , 4 , 6 , 8 ). The reduced estrogen level and other aging processes associated with menopause in women above 50 years of age are factors that increase the risk of stroke ( 3 , 13 ).…”
Section: Introductionmentioning
confidence: 99%
“… 10 When ACA is diagnosed, atherosclerosis treatment can be initiated by the appropriate professional, with the objective of repairing or mitigating acute or chronic ischemic lesions, thereby preventing serious manifestations and preserving the patient’s quality of life. 11 …”
Section: Introductionmentioning
confidence: 99%